2021
DOI: 10.3390/nano11051173
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Characterization of RP-ALD SiO2 Thin Films with Different Oxygen Plasma Powers

Abstract: In this study, silicon oxide (SiO2) films were deposited by remote plasma atomic layer deposition with Bis(diethylamino)silane (BDEAS) and an oxygen/argon mixture as the precursors. Oxygen plasma powers play a key role in the quality of SiO2 films. Post-annealing was performed in the air at different temperatures for 1 h. The effects of oxygen plasma powers from 1000 W to 3000 W on the properties of the SiO2 thin films were investigated. The experimental results demonstrated that the SiO2 thin film growth per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Zhang showed that compared with other modification methods, the thickness of ALD-deposited SiO 2 nanofilms can be precisely controlled at the nanoscale, and the film thickness increases linearly with the number of ALD cycles. 32 , 33 In the current study, SE findings also confirmed the abovementioned point. The thickness of the SiO 2 nanofilms deposited at 200 °C demonstrated a linear relationship with a deposition rate of 0.059 ± 0.005 nm/cycle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Zhang showed that compared with other modification methods, the thickness of ALD-deposited SiO 2 nanofilms can be precisely controlled at the nanoscale, and the film thickness increases linearly with the number of ALD cycles. 32 , 33 In the current study, SE findings also confirmed the abovementioned point. The thickness of the SiO 2 nanofilms deposited at 200 °C demonstrated a linear relationship with a deposition rate of 0.059 ± 0.005 nm/cycle.…”
Section: Discussionsupporting
confidence: 90%
“…The film thickness was measured using SE (M-2000v, J A Woollam, USA) at an incidence angle of 65° and the wavelength region from 200 to 2000 nm to indirectly reflect the thickness of SiO 2 nanofilms. 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…After dielectric deposition, the PDMS layer is mechanically removed. For ALD, thermal deposition at low temperatures is preferred as it produces higher-quality SiO2 59 . Additionally, plasma ALD can increase the thickness of the photoresist layer.…”
Section: Nanopore Fabricationmentioning
confidence: 99%
“…This conclusion is consistent with other reports. [33,34] Therefore, the thickness of the film could be precisely adjusted by controlling the number of cycles. In contrast to linear ALD, Z-Prime Plus was coated manually, and its thickness depended on the number of layers.…”
Section: Thickness Of Sio 2 Filmsmentioning
confidence: 99%
“…[ 20 ] ALD may produce nanoscale films with high precision, [ 21 ] controllable thickness, and extreme uniformity. [ 22,23 ] ALD has already been widely used to deposit films on a variety of materials and is thus expected to overcome the drawbacks of other common SiO 2 film deposition methods because of the following ALD advantages. [ 24 ] The films are deposited by gas–solid chemical reactions; thus, the films are firmly and stably bonded with the substrate.…”
Section: Introductionmentioning
confidence: 99%